2020
DOI: 10.7874/jao.2020.00115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Animal Models for Meniere’s Disease: A Mini-Review

Abstract: Several novel animal models that represent the pathophysiological process of endolymphatic hydrops (ELH) of Meniere’s disease (MD) have been developed. Animal models are important to identify and characterize the pathophysiology of ELH and to corroborate molecular and genetic findings in humans. This review of the current animal models will be useful in understanding the pathophysiology of and developing proper treatments for MD. Surgical animal models will be replaced by medication-induced animal models. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…Current existing animal models can resemble the dilation of SM and low-frequency hearing loss. It is widely accepted that the EH animal models, created through surgical operation, medication application, or their combination, can reproduce the chronic phase of MD ( Seo and Brown, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Current existing animal models can resemble the dilation of SM and low-frequency hearing loss. It is widely accepted that the EH animal models, created through surgical operation, medication application, or their combination, can reproduce the chronic phase of MD ( Seo and Brown, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Meniere's disease, histopathological temporal bone studies have shown that circulatory disturbances might cause abnormal endolymph homeostasis. [51,52]. A greater volume of the endolymphatic fluid causes the cochlear lateral wall, including the capillary network, to be compressed against the bony labyrinth, and ischemic reperfusion damage can be caused by this increase in cochlear outflow resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the administration of vasopressin acts on the V2-aquaporin 2 receptor couple present in the endolymphatic sac to generate hydrops. Although these models do not always induce auditory or vestibular deficits in animals, they nevertheless allow confirmation that local administrations of compounds likely to act on the osmolarity of the endolymph, such as diuretics, are capable of significantly reducing hydrops [ 34 , 35 , 36 ]. The degree of predictivity of these study models must however be balanced by the fact that the etiology of Menière disease is certainly multiple, and that hydrops is perhaps a histological correlate which is not mandatory to the expression of the vestibular syndrome.…”
Section: Animal Models Of Peripheral Vestibulopathiesmentioning
confidence: 99%